Le corrispondenze familiari nell'archivio Dessí - Andrei, Chiara (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2003)
The volume presents a specific historical-geographical background, that of Sardinia in the '30s and '40s, of the Scuola Normale in Pisa, of Ferrara in the first post-war period, against which it shapes the figure of a writer, of his formation and of his first steps in writing. Around the figure of Giuseppe Dessí, one of the most refined and secluded narrators of the second half of our twentieth century, are presented those of his father, his brother, his companions, his friends. A world to be discovered, a complexity of relationships to be unravelled, thanks to over 1400 letters preserved in the Contemporary Archive of the Gabinetto Vieusseux in Florence, of which the cataloguing and a wide range of contents are offered here.